Relationship between Daytime Sleepiness and Intrinsically Photosensitive Retinal Ganglion Cells in Glaucomatous Disease - Carolina P. B. Gracitelli; Gloria Liliana Duque-Chica; Ana Laura de Araújo Moura; Marina Roizenblatt; Balazs V. Nagy; Geraldine Ragot de Melo; Paula Delegrego Borba; Sérgio H. Teixeira; Sergio Tufik; Dora Fix Ventura; Augusto Paranhos (Journal of Ophthalmology)
Patients with glaucoma showed to have higher daytime sleepiness measured by Epworth sleepiness scale. In addition, this symptom was associated with pupillary reflex and polysomnography parameters. These ipRGC functions might be impaired in patients with glaucoma, leading to worse quality of life.